Characterizing the symptom of misplacing objects in people with dementia: findings from an online tracking tool. (30th January 2019) - McGarrigle, Lisa; Howlett, Susan E.; Wong, Helen; Stanley, Justin; Rockwood, Kenneth
ABSTRACT: Objectives: Misplacing objects is often reported as a clinically important symptom in dementia. Here we explored misplacing objects in relation to dementia type and stage in an online sample of individuals with dementia and their caregivers. Methods: Participants were recruited from www.dementiaguide.com, a web-based tracker for common dementia symptoms. Users provided information about symptoms that they selected as important for monitoring. We analysed cross-sectional data from respondents who tracked at least three symptoms, which allowed for staging dementia severity. Results: Of 2, 775 users with three-plus symptoms, 787 (28%) identified misplacing objects for symptom tracking. Misplacing objects was monitored by users across all stages of dementia, but was more prevalent in mild and severe dementia. Three common clinical subtypes of misplacing were investigated: lost & found (forgetting the location of items), hidden away (hiding items so others would not find them), and odd places (putting items in usual spots). Of the 787, 96% targeted lost & found, the most frequent type. Odd places (targeted in 56%) significantly increased with dementia severity (p < 0.001). Misplacing objects was most strongly associated with the symptoms of interaction with strangers (OR 4.60, 95% CI: 3.20-6.62), reading (3.68: 2.86-4.73), shopping (3.55: 2.73-4.61) and travel/vacationing (3.31: 2.54-4.31). Conclusions: Misplacing objects was most often selected for tracking in mild and severe stages of dementia. As disease advances, misplacing more often reflects odd placement of objects rather than their simple loss. Misplacing objects may be a clinically important therapeutic target for improving patients' quality of life and lessening caregiver burden.